Mobile Health in Adherence to Oral Anticancer Drugs: A Scoping Review. Issue 1 (January 2021) - Gambalunga, Francesca; Iacorossi, Laura; Notarnicola, Ippolito; Serra, Valeria; Piredda, Michela; De Marinis, Maria Grazia
Abstract : In oncology, adherence to oral antineoplastic medication is a key element of treatment, on which the success of any therapeutic intervention depends. Given their widespread use in clinical practice, it is important to identify tools that can facilitate the monitoring and self-management of the patient at home, to avoid the consequences of employing ineffective treatment. One of the tools available today to take action on this phenomenon is mobile health technology. The aim of this review is to describe published studies relating to the use of mobile health to promote adherence to oral antineoplastic medication. This scoping review was conducted using the framework proposed by Arksey and O'Malley, adapted according to Levac et al. Of 1320 articles identified, only seven met the eligibility criteria and therefore were included in the review. All seven articles involved the use of digital means to measure adherence to treatment, patient satisfaction, acceptability and feasibility of the digital means used, and presence of symptoms, but not the effectiveness of the digital instrument used. In conclusion, the use of digital means to assist adherence of cancer patients to oral antineoplastic medication is widely recognized, but its effectiveness in clinical practice is poorly supported by the nature of the published studies. Abstract : Supplemental digital content is available in the text.